การคาดคะเนระดับความล่าช้าในการดำเนินงานก่อสร้างรถไฟฟ้ามหานคร - กระจ่างตา นันท์ธิดา; ดำริห์อนันต์ จิรวัฒน์ (Thai Journal of Science and Technology, 2019)
A regression equation was developed to predict delay levels in construction projects for the Metropolitan Rapid Transit (MRT) system. Factors delaying project completion were examined. Recommendations for controlling lateness were proposed. Data were gathered from the MRT Purple Line project (Bang Yai - Rat Burana, Bang Yai - Bang Sue Section). Samples were 140 project staff engineers and technicians. Data were gathered by questionnaire and analyzed by stepwise regression, with lateness factors identified. Results were that the regression equation was composed of six variables contributing to the delays. These findings suggest that the principles of lean construction and application of new technologies might be introduced to resolve future challenges.